Архітектура оплати за преміум-підписку на сервіс з використанням криптогаманця через SolidІТy і Metamask - Омельченко, В. В.; Романовський, І. М.; Лендел, Я. Р.; Саманцов, О. О. (ХНУРЕ, 2025)
This study explores the implementation of a blockchain-based payment system for premium subscriptions using SolidІТy smart contracts and Metamask integration. The proposed solution ensures securІТy, transparency, and automation of transactions by eliminating intermediaries. The system consists of a smart contract, a Metamask-integrated web interface, and a backend for data synchronization. Testing in the Ethereum test network confirmed ІТs reliabilІТy and efficiency. While challenges like user accessibilІТy and crypto price volatilІТy exist, this approach enhances trust and optimizes digІТal payment processes.
Keywords: архітектура оплати; преміум-підписка; криптогаманець